2010
DOI: 10.5539/ijb.v2n2p222
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis and Combining Ability Analysis for Yield and Related-Yield Traits in Hybrid Rice

Abstract: Study of combining ability and heterosis were conducted on 12 F1 hybrids along with seven rice genotypes (three
cytoplasmic male sterile lines and four restorer varieties) to know the pattern of inheritance of some
morphological traits for selecting superior genotypes. The experiment was carried out according to line x tester
mating design, during 2007-08. Analysis of variance revealed significant differences among genotypes, crosses,
lines, testers and line x tester interactions for tiller…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 10 publications
15
22
0
Order By: Relevance
“…For rest of the traits studied, female x male component of variances were significant at 0.1% probability level (p = 0.001), indicating that female parents interacted sufficiently with the male parents. These results are in confirmation with the findings of Akter et al (2010), and Bagheri and Jelodar (2010) in rice, who also reported that female parents interacted significantly with the male parents. Combining ability variances in the present study revealed that the magnitude of additive genetic variance (σ 2 A) was higher than dominance genetic variance (σ 2 D) for the characters, days to 50% flowering, days to maturity, plant height, number of effective tillers per plant, 100 grain weight, kernel length before cooking and kernel breadth before cooking, suggesting the preponderance of additive gene action for these traits.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…For rest of the traits studied, female x male component of variances were significant at 0.1% probability level (p = 0.001), indicating that female parents interacted sufficiently with the male parents. These results are in confirmation with the findings of Akter et al (2010), and Bagheri and Jelodar (2010) in rice, who also reported that female parents interacted significantly with the male parents. Combining ability variances in the present study revealed that the magnitude of additive genetic variance (σ 2 A) was higher than dominance genetic variance (σ 2 D) for the characters, days to 50% flowering, days to maturity, plant height, number of effective tillers per plant, 100 grain weight, kernel length before cooking and kernel breadth before cooking, suggesting the preponderance of additive gene action for these traits.…”
Section: Resultssupporting
confidence: 82%
“…Significant negative GCA and SCA effects for days to 50 per cent flowering in rice have also reported by Tiwari et al (2011) and Latha et al (2013). Bagheri and Jelodar (2010) observed that IR-58025A exhibited undesirable GCA effect, but most of its crosses revealed desirable SCA effects for days to 50% flowering. The significant negative estimate of GCA effect for days to maturity among the CMS lines was recorded by IR-68897A, whereas amongst the male parents, the highest significant negative value of GCA effect was observed in Pusa Sugandh-3 followed by Pusa Sugnadh-5 and Pusa 2517-2-51-1.…”
Section: Combining Ability Effects For Yield and Yield Traitsmentioning
confidence: 89%
See 2 more Smart Citations
“…Significant mean squares due to lines and tester for a particular trait indicate the prevalence of additive variance. However, significant difference due to interactions of line × tester for some of the characters suggested the importance of both additive and non-additive variance for these traits (Bagheri and Babaeian 2010). Thus both additive and non additive gene actions should be studied for improving yield related traits.…”
Section: Resultsmentioning
confidence: 99%